Introduction: Authority Building in International Administered Territories. Issue 4 (2nd October 2017) - Bonacker, Thorsten; Brodocz, André
ABSTRACT: This introduction to the special section on "Authority Building in International Administered Territories" begins by summarizing the relevant literature on international administrations. To conceptualize authority building as an ongoing process in which international and local actors confirm – or refuse – authority claims, secondly, two types of authority are differentiated: 'interpretative authority' and 'performing authority'. This sociological conceptualization of authority building allows, thirdly, a discussion on the restrictions and challenges that international administrations face in their attempts to establish authority on the ground. Finally, an overview of the section's articles is provided.